Elovl5 Expression in the Central Nervous System of the Adult Mouse - Balbo, Ilaria; Montarolo, Francesca; Boda, Enrica; Tempia, Filippo; Hoxha, Eriola (Frontiers in Neuroanatomy, 2021)
ELOVL5 (Elongase of Very-Long Fatty Acid 5) gene encodes for an enzyme that elongates long chain fatty acids, with a marked preference for polyunsaturated molecules. In particular, it plays an essential role in the elongation of omega-3 and omega-6 fatty acids, precursors for long-chain polyunsaturated fatty acids (PUFAs). Mutations of ELOVL5 cause the spino-cerebellar ataxia type 38 (SCA38), a rare autosomal neurological disease characterized by gait abnormality, dysarthria, dysphagia, hyposmia and peripheral neuropathy, conditions well represented by a mouse model with a targeted deletion of this gene (Elovl5-/- mice). However, the expression pattern of this enzyme in neuronal and glial cells of the central nervous system (CNS) is still uninvestigated. This work is aimed at filling this gap of knowledge by taking advantage of an Elovl5-reporter mouse line and immunofluorescence analyses on adult mouse CNS sections and glial cell primary cultures. Notably, Elovl5 appears expressed in a region- and cell type-specific manner. Abundant Elovl5-positive cells were found in the cerebellum, brainstem, and primary and accessory olfactory regions, where mitral cells show the most prominent expression. Hippocampal pyramidal cells of CA2/CA3 where also moderately labeled, while in the rest of the telencephalons Elovl5 expression was high in regions related to motor control. Analysis of primary glial cell cultures revealed Elovl5 expression in oligodendroglial cells at various maturation steps and in microglia, while astrocytes showed a heterogeneous in vivo expression of Elovl5. The elucidation of Elovl5 CNS distribution provides relevant information to understand the physiological functions of this enzyme and its PUFA products, whose unbalance is known to be involved in many pathological conditions.